Response of Weaner Rabbits to Concentrate Supplemented with Varying Levels of Syndrella nodiflora Forage - Omoikhoje, S.O.; Bamgbose, A.M.; Aruna, M.B.; Animashahun, R.A. (Pakistan Journal of Nutrition, 2006)
A ten-week feeding trial was conducted to evaluate the effect of feeding varying levels of forage ( Syndrella nodiflora ) on the performance, haematology, and serum chemistry of twenty-four weaner rabbits. Six rabbits each were assigned to each dietary treatment (A, B, C and D) in three replicate groups of two rabbits each, in a completely randomized design (CRD). Performance data of weaner rabbits reflect that average final live weight, weight gain, feed intake and feed conversion ratio were significantly (P< 0.05) higher in rabbits fed diets B and C than those on diets A and D (0 and 75% supplement). All the heamatological and serum chemistry indices assayed were not significantly (P>0.05) affected by the dietary treatments. Therefore, Syndrella nodiflora can be used to supplement rabbit diets up to 50% to enhance performance without any adverse effect.